2006
DOI: 10.1093/annhyg/mel073
|View full text |Cite
|
Sign up to set email alerts
|

Physical Collection Efficiency of Filter Materials for Bacteria and Viruses

Abstract: The purpose of this study was to determine the physical collection efficiency of commercially available filters for collecting airborne bacteria, viruses, and other particles in the 10-900 nm (nanometer) size range. Laboratory experiments with various polytetrafluoroethylene (PTFE), polycarbonate (PC) and gelatin filters in conjunction with Button Inhalable samplers and three-piece cassettes were undertaken. Both biological and non-biological test aerosols were used: Bacillus atrophaeus, MS2, polystyrene latex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…Gentry et al (1982) found that the penetration of Nuclepore filters with 2 and 5 μ m pore size varied from 40% to 76% (~23%–60% collection efficiencies) and 70%–86% (~14%–30% collection efficiencies) at face velocities in range of 0.8–6.6 cm s −1 . Burton et al (2007) also found that the polycarbonate filter showed low collection efficiency for particles <100 nm. The lowest collection efficiencies, 49% and 22% were observed for 1 and 3 μ m pore size polycarbonate filter when a flow rate of 4 l min −1 was used.…”
Section: Discussionmentioning
confidence: 89%
“…Gentry et al (1982) found that the penetration of Nuclepore filters with 2 and 5 μ m pore size varied from 40% to 76% (~23%–60% collection efficiencies) and 70%–86% (~14%–30% collection efficiencies) at face velocities in range of 0.8–6.6 cm s −1 . Burton et al (2007) also found that the polycarbonate filter showed low collection efficiency for particles <100 nm. The lowest collection efficiencies, 49% and 22% were observed for 1 and 3 μ m pore size polycarbonate filter when a flow rate of 4 l min −1 was used.…”
Section: Discussionmentioning
confidence: 89%
“…While Griffin et al 14 collected air samples directly onto a 0.02-μm pore size filter, we used a 0.2-μm pore size filter with lower pressure drop due to concerns about noise from the sampling pump in indoor, occupied environments. Based on studies of membrane filters with similar or larger pore sizes than 0.2 μm, 3537 we expect the collection efficiency to be >99% for both virus- and bacteria-sized particles, so the use of filters with different pore sizes should not bias the comparison. The VBR of 1.4 in outdoor air in Blacksburg, Virginia is 7% higher than in the Caribbean and 58% lower than in Korea.…”
Section: Resultsmentioning
confidence: 99%
“…The different criteria for selection of an appropriate surrogate for B. anthracis endospores have been already proposed; among them, a risk of use, genetic and morphological similarity to B. anthracis , and response to various chemical and environmental challenges seemed to be most important (Greenberg et al 2010). An aerodynamic diameter of B. atrophaeus endospore is about 0.9 μm and is slightly smaller when compared to B. anthracis endospores (Burton et al 2007; Carrera et al 2006). B. atrophaeus is considered as nonpathogenic and is classified as a BSL-1 organism.…”
Section: Discussionmentioning
confidence: 99%